Criminal Code Draft and Protection for Victims of Gender Based Violence - Eddyono, Sri Wiyanti (Yayasan Jurnal Perempuan, 2018)
This paper analysis whether the Criminal Code Draft is oriented towards the interests and protection of the rights of victims especially women victims of gender-based violence. This paper uses juridical or normative research methods, through analysis on articles in the Criminal Code Draft. This study uses analytical framework of feminist legal theory which put law as a political product and often neglects the interests of women victims of violence that vary. This paper finds that the main orientation of the Criminal Code Draft is the interests of the perpetrator and the community, but not explicitly oriented to the victim's interests. It is assumed that with reference to the public interest then it has been victim-oriented. The victim is still seen as the party who helps to reveal the case alone, not the party who has suffered the loss so they need protection and reparation. The responsibility of the perpetrator is addressed to meet the interests of a sense of community justice, not a victim. In addition, some of the regulatory articles on criminal offenses still contain problems because the Criminal Code Bill prefer to compiles several laws outside the Criminal Code but does not revise articles which based on the experiences of the victims is difficult to implement, such as the arrangement of PKDRT (domestic violence). Furthermore, there are still articles that victimize victims by criminalizing those who are actually victims of gender-based violence.